Folklore as an Intergrated Discipline and Its Current Research Trends - Malaiwong, Pawin (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2013)
In this research paper, I want to examine the principles upon which the academic study of folklore, specifically in the United States, have been progressively established over years since 1888 when the American Folklore Society (AFS), the first professional folklore body, was founded. I also want to reconsider the direction of folklore studies indicated by those principles. I am going to examine the theories and methodological assumptions of the founders of American folklore studies by looking at their ideas in context and by exploring how those ideas have affected the ways in which folklore has been studied, preserved and presented. I hope this research paper will provide a comprehensive viewpoint of the theoretical and historical contexts for the development of folklore studies in America in a way that would be readily accessible to both folklorists and scholars outside the discipline. ในบทความวิจัยชิ้นนี้ ผู้เขียนต้องการพิจารณาหลักการทางคติชนวิทยา โดยเฉพาะอย่างยิ่งที่เกิดขึ้นในประเทศสหรัฐอเมริกา ภายหลังการจัดตั้งสมาคมคติชนวิทยาอย่างเป็นทางการในปี ค.ศ.1888 ผู้เขียนยังต้องการศึกษาทิศทางของงานวิจัยด้านคติชนวิทยาในปัจจุบัน เพื่อให้บรรลุวัตถุประสงค์ดังกล่าว ผู้เขียนได้รวบรวมทฤษฎีและตัวอย่างกลยุทธ์ของงานวิจัยเพื่อชี้ให้เห็นขอบเขตและแนวคิดที่ถูกครอบคลุมอยู่ภายใต้การศึกษาแบบคติชนวิทยา ตลอดจนวิธีนำเสนอของนักคติชนวิทยาที่ผสมผสานความคิดจากศาสตร์แขนงอื่น วัตถุประสงค์คือเพื่อนำองค์ความรู้มาต่อยอดเป็นการศึกษาแบบบูรณาการ ผู้เขียนหวังเป็นอย่างยิ่งว่าบทความวิจัยชิ้นนี้จะนำเสนอมุมมองวงกว้างเชิงประวัติศาสตร์การพัฒนาของคติชนวิทยาในประเทศสหรัฐอเมริกา ที่จะเป็นประโยชน์ต่อทั้งนักคติชนวิทยาเองและนักวิชาการในสาขาต่างๆ